Disappearing His deflection. Electrophysiological evidence for conduction defect within the His bundle. - Csapo, G (1978)
A change in the voltage and character of the His bundle deflection following premature atrial stimuli was observed and analysed in 5 of 95 patients having intracardiac conduction studies because of AV conduction disturbances. Of these 5 patients, 3 had spontaneous block within the His bundle, 2 of them showing block in other segments of the conduction system. With increasing prematurity of programmed atrial stimuli, there was a progressive decrease in the voltage of the His deflection, followed by a split His deflection, and finally disappearance of the His deflection. The voltage of the His deflection was also reduced in sinus beats following spontaneous His bundle premature beats. Similarly, during atrial stimulation at increasing rates, the His deflection decreased in voltage, split, and finally disappeared, but when Wenckebach periods appeared the His deflection reappeared in the first paced beat after the dropped beat. The preceding H-H interval was the only electrophysiological variable consistently related to the changes in the His deflection. These changes in His deflection can be explained electrophysiologically as the result of a conduction disturbance within the His bundle. The clinical significance of the phenomenon is discussed. The occurrence of this phenomenon during a conduction study makes it difficult or even impossible to localise the AV block precisely.